Pengaruh Faktor Internal Dan Eksternal Terhadap Keputusan Perusahaan untuk Melakukan Initial Public Offering (IPO): Studi Empiris Pada Perusahaan Start-Up di Indonesia - Andriani, Juwita (CV. ITTC INDONESIA, 2023)
The start-up business in Indonesia is growing with the emergence of many new start-up companies in various fields such as technology, finance, health, and so on. Start-up companies are also increasingly seen as a sector that has great potential to become the engine of Indonesia's economy in the future, to support the growth of start-up companies, one of the strategies that is usually carried out is to carry out an Initial Public Offering (IPO). This research will help fill in the gaps in the literature on external factors influencing a company's decision to go IPO. Thus, it is hoped that the results of this research can make a positive contribution to the development of start-up businesses in Indonesia and assist start-up companies in making the right decisions regarding IPOs. The population in this study are all start-up companies in Indonesia. The samples in this study are Gojek, Grab, Ovo and Shoppe. This study used a purposive sampling technique. The sample in this study is 108. The data analysis technique in this study uses PLS with the results of the research that financial performance has a positive effect on a company's decision to conduct an Initial Public Offering (IPO), company size has a positive effect on a company's decision to conduct an Initial Public Offering (IPO). ), capital market conditions have a positive effect on a company's decision to conduct an Initial Public Offering (IPO), and government policies have a positive effect on a company's decision to conduct an Initial Public Offering (IPO).